2010
DOI: 10.1681/asn.2010020181
|View full text |Cite
|
Sign up to set email alerts
|

The Anti-Fibrotic Effect of Mycophenolic Acid–Induced Neutral Endopeptidase

Abstract: Mycophenolic acid (MPA) appears to have anti-fibrotic effects, but the molecular mechanisms underlying this are unknown. We prospectively studied 35 stable kidney transplant recipients maintained on cyclosporine and azathioprine. We converted 20 patients from azathioprine to enteric-coated mycophenolate sodium (EC-MPS) and continued the remaining 15 patients on azathioprine. Exploratory mRNA expression profiling, performed on five randomly selected EC-MPS patients, revealed significant upregulation of neutral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 50 publications
1
22
0
Order By: Relevance
“…Lastly, results of an ad hoc linear regression analysis of calculated CrCl suggest that the inferior long-term results observed in group B were specifically a result of early underimmunosuppression with TAC and MMF (but apparently not because of steroid avoidance). Two recent studies (13,14) show that early conversion from TAC to sirolimus does not result in improved glomerular filtration rate and less CAI, and another study (15) indicates that MMF offers protection against graft fibrosis, each supporting the results of our ad hoc analysis.…”
Section: Discussionsupporting
confidence: 76%
“…Lastly, results of an ad hoc linear regression analysis of calculated CrCl suggest that the inferior long-term results observed in group B were specifically a result of early underimmunosuppression with TAC and MMF (but apparently not because of steroid avoidance). Two recent studies (13,14) show that early conversion from TAC to sirolimus does not result in improved glomerular filtration rate and less CAI, and another study (15) indicates that MMF offers protection against graft fibrosis, each supporting the results of our ad hoc analysis.…”
Section: Discussionsupporting
confidence: 76%
“…Owing to the fact that there was no difference in incidence of acute rejection with respect to increased MMF exposure in our study, we believe that there may be a significant contribution of non-immune mechanisms in retardation of IF/TA in patients with higher MMF. In line with this, in many experimental models it has been shown that MMF has antiproliferative and antifibrotic effects 13 26 27. In the study of Jiang et al using rat renal ischaemia reperfusion injury, a time-dependent and dose-dependent correlation of higher MMF dose with better renal function and lower interstitial fibrosis was demonstrated.…”
Section: Discussionmentioning
confidence: 73%
“…Retrospective studies of renal recipients who were treated with MMF comparing azathioprin showed that MMF-treated patients had significantly less chronic allograft dysfunction 8 9. Besides being associated with lower acute rejection rates as compared to azathioprin,10 11 evidence from animal and human studies suggests that MMF may also exert direct antifibrotic properties due to its antiproliferative action on non-immune cells, including renal tubular cells and vascular smooth muscle cells 12 13…”
Section: Introductionmentioning
confidence: 99%
“…5 It has also been demonstrated in vivo to down-regulate production of transforming growth factor beta, which is thought to result in reduced deposition of extracellular matrix and hence is a promising therapy in fibrotic disorders. 6 MMF has been associated with improvement in skin thickening in several observational studies in SSc, [7][8][9] and more recently, in the Scleroderma Lung Study II (SLS II). 10 This randomized controlled study compared the effect of CYC and MMF on forced vital capacity (FVC) in ILD in patients with diffuse or limited SSc.…”
Section: Introductionmentioning
confidence: 99%